Collecting duct carcinoma of the kidney: Clinicopathological profile and outcomes - Abhilash Cheriyan; Rajiv Paul Mukha; Shailaja Balakumar; Nirmal Thampi John; Santosh Kumar (Urological Science, 2023)
Purpose: Collecting duct carcinoma of the kidney (CDC) is an aggressive subtype of renal cell carcinoma with a dismal prognosis. The available knowledge concerning optimal management is still unclear. We report the largest single-institutional experience in the management of CDC. Materials and Methods: All the cases of CDC which were diagnosed at our center following a radical or partial nephrectomy in the past 15 years were included. Treatment details, radiological features, and histological features were reviewed. Descriptive statistics were used to show the clinicopathological profile and management of these patients, and Kaplan–Meier overall survival (OS) estimate was calculated. Results: Eighteen patients who were diagnosed and underwent the primary intervention at our center were included. The median age of patients was 40 years, with a male-to-female ratio of 5:1. Typical histopathological features included high-grade nuclear features, stromal desmoplasia, and tubular architecture. Surgery was the primary modality of treatment. Five (28%) patients who had metastases received adjuvant therapy, three received interferon-alpha therapy, and two received adjuvant chemotherapy with gemcitabine and cisplatin. The median follow-up was 19 months (range: 3–46 months). Kaplan–Meier OS estimate was 68% at 1 year and 48% at 3 years. Conclusion: CDC of the kidney often presents at an advanced stage, and has a poor prognosis. Survival remains poor despite surgery and adjuvant therapy.